Longitudinal association of alcohol use with HIV disease progression and psychological health of women with HIV. - Ghebremichael, Musie; Paintsil, Elijah; Ickovics, Jeannette R; Vlahov, David; Schuman, Paula; Boland, Robert; Schoenbaum, Ellie; Moore, Janet; Zhang, Heping (AIDS care, 2009)
We evaluated the association of alcohol consumption and depression, and their effects on HIV disease progression among women with HIV. The study included 871 women with HIV who were recruited from 1993-1995 in four US cities. The participants had physical examination, medical record extraction, and venipuncture, CD4+T-cell counts determination, measurement of depression symptoms (using the self-report Center for Epidemiological Studies-Depression Scale), and alcohol use assessment at enrollment, and semiannually until March 2000. Multilevel random coefficient ordinal models as well as multilevel models with joint responses were used in the analysis. There was no significant association between level of alcohol use and CD4+ T-cell counts. When participants were stratified by antiretroviral therapy (ART) use, the association between alcohol and CD4+ T-cell did not reach statistical significance. The association between alcohol consumption and depression was significant (p<0.001). Depression had a significant negative effect on CD4+ T-cell counts over time regardless of ART use. Our findings suggest that alcohol consumption has a direct association with depression. Moreover, depression is associated with HIV disease progression. Our findings have implications for the provision of alcohol use interventions and psychological resources to improve the health of women with HIV.
Keywords: Adult; Alcohol Drinking; Alcoholism; Anti-Retroviral Agents; CD4 Lymphocyte Count; Cocaine-Related Disorders; Depressive Disorder; Disease Progression; Epidemiologic Methods; Female; HIV Infections; Humans; Risk Factors; Substance Abuse, Intravenous; United States